2021
DOI: 10.1016/j.celrep.2021.109267
|View full text |Cite
|
Sign up to set email alerts
|

Streptococcus pneumoniae binds to host GAPDH on dying lung epithelial cells worsening secondary infection following influenza

Abstract: SUMMARY Streptococcus pneumoniae (Spn) alone and during co-infection with influenza A virus (IAV) can result in severe pneumonia with mortality. Pneumococcal surface protein A (PspA) is an established virulence factor required for Spn evasion of lactoferricin and C-reactive protein-activated complement-mediated killing. Herein, we show that PspA functions as an adhesin to dying host cells. We demonstrate that PspA binds to host-derived glyceraldehyde-3-phosphate d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
28
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 30 publications
(33 citation statements)
references
References 64 publications
(73 reference statements)
3
28
0
Order By: Relevance
“…In in vivo experiments, co-infection appears to be adverse for the host, caused by the IAV induced expression of type I interferons suppressing the bacterial clearance by disturbed recruitment of immune cells ( LeMessurier et al., 2020 ; Park et al., 2021 ). On the other hand, type I interferons increase the expression of tight junction proteins and decrease the expression of PAFr, reducing pneumococcal uptake and hindering transmigration ( LeMessurier et al., 2013 ).…”
Section: Discussionmentioning
confidence: 99%
“…In in vivo experiments, co-infection appears to be adverse for the host, caused by the IAV induced expression of type I interferons suppressing the bacterial clearance by disturbed recruitment of immune cells ( LeMessurier et al., 2020 ; Park et al., 2021 ). On the other hand, type I interferons increase the expression of tight junction proteins and decrease the expression of PAFr, reducing pneumococcal uptake and hindering transmigration ( LeMessurier et al., 2013 ).…”
Section: Discussionmentioning
confidence: 99%
“…A recent study has highlighted the role of mammalian cell surface recruited GAPDH in host pathogen interaction. Host GAPDH on surface of dying lung epithelial cells was found to interact with Strepococcus pneumoniae resulting in secondary infection following influenza infection [ 47 ]. This study demonstrated that endogenous GAPDH was recruited onto the surface of dying lung epithelial cells which had been infected with either, Influenza A virus (IAV) or Streptococcus pneumoniae .…”
Section: Discussionmentioning
confidence: 99%
“…In our studies that identified PspA as having affinity to lactate dehydrogenase and GAPDH, it was observed that PspA also had affinity to numerous other host proteins (Park et al, 2021a;Park et al, 2021b). Among these was the filamentous protein vimentin, which has been implicated as a key ligand for group B Streptococci and E. coli with regard to their ability to gain access to the central nervous system (Deng et al, 2019).…”
Section: Other Interactionsmentioning
confidence: 92%
“…Curates PC residues on pneumococcal surface (Gosink et al, 2000;Hermoso et al, 2005) Choline McDaniel et al, 1986;McDaniel et al, 1987;Shaper et al, 2004;Mukerji et al, 2012;Park et al, 2021a;Park et al, 2021b) Pneumococcal choline-binding protein A…”
Section: Name Abbreviation Functionmentioning
confidence: 99%